New insights in ubiquitin-dependent Wnt receptor regulation in tumorigenesis - Tsukiyama, Tadasuke (In vitro cellular & developmental biology. Animal, 2024)
Wnt signaling plays a crucial role in embryonic development and homeostasis maintenance. Delicate and sensitive fine-tuning of Wnt signaling based on the proper timings and positions is required to balance cell proliferation and differentiation and maintain individual health. Therefore, homeostasis is broken by tissue hypoplasia or tumor formation once Wnt signal dysregulation disturbs the balance of cell proliferation. The well-known regulatory mechanism of Wnt signaling is the molecular reaction associated with the cytoplasmic accumulation of effector β-catenin. In addition to β-catenin, most Wnt effector proteins are also regulated by ubiquitin-dependent modification, both qualitatively and quantitatively. This review will explain the regulation of the whole Wnt signal in four regulatory phases, as well as the different ubiquitin ligases and the function of deubiquitinating enzymes in each phase. Along with the recent results, the mechanism by which RNF43 negatively regulates the surface expression of Wnt receptors, which has recently been well understood, will be detailed. Many RNF43 mutations have been identified in pancreatic and gastrointestinal cancers and examined for their functional alteration in Wnt signaling. Several mutations facilitate or activate the Wnt signal, reversing the RNF43 tumor suppressor function into an oncogene. RNF43 may simultaneously play different roles in classical multistep tumorigenesis, as both wild-type and mutant RNF43 suppress the p53 pathway. We hope that the knowledge obtained from further research in RNF43 will be applied to cancer treatment in the future despite the fully unclear function of RNF43.